Russian language as a means of cultural representation in the space of the I.V. Savitsky Museum in Nukus - Genzhebaeva, Gulbakhar Kurbanbaevna (The Lingua Spectrum, 2026)
The article is devoted to a comprehensive analysis of the Russian language as a means of cultural representation in the museum space formed around the unique collection of State Museum of Arts of the Republic of Karakalpakstan named after I.V. Savitsky. The relevance of the study is обусловлена the increasing role of language as a tool for interpreting cultural heritage in the context of globalization, digitalization, and the intensification of intercultural dialogue. The aim of the research is to identify and substantiate the functional potential of the Russian language in museum communication, demonstrating that it performs not only an informative but also a conceptual and meaning-forming function. The research material includes open digital sources such as catalog cards of artworks, institutional descriptions, exhibition texts, and announcements related to the museum. The methodological framework is based on genre analysis, content analysis, and discourse analysis, which make it possible to reveal the specifics of language functioning in various types of museum texts. It is established that the Russian language implements six key functions: nominative, interpretative, historicizing, representational, mediating, and communicative. The article concludes that Russian plays a significant role as a mediator between the local culture of Karakalpakstan and the international cultural space, ensuring accessibility of cultural meanings to a wide audience.